Pharmacokinetics of Three Organic Nitrates in Chinese Healthy Male Volunteers - Chen, Jun; Jiang, Xin Guo; Cai, Lei; Lu, Wei; Gao, Ke Pan; Shi, Zheng Qi; Zhang, Qi Zhiang (Arzneimittelforschung, 2004)
Eighteen Chinese male subjects completed a single-blind, randomized, three-treatment, three-period, cross-over study. In each treatment phase, subjects received a single dose of 20 mg isosor-bide dinitrate (CAS 87-33-2, ISDN) intravenous infusion, 20 mg isosorbide 5-mononitrate (CAS 16051-77-7, 5-ISMN) tablet or 20 mg isosorbide 5-mononitrate intravenous infusion. Each consecutive dosing was separated by a washout period of 7 days. Following each dosing, venous blood samples were collected over a period of 16 h. Plasma concentrations of ISDN and its two active metabolites isosorbide 2-mononitrate (2-ISMN), 5-ISMN had been measured by a validated gas chromatographic method. Various pharmacokinetic parameters including AUC0.ti AUC0–∞, Cmax, tmax, t1/2, Kelm and MRT were determined for the three formulations and found to be in good agreement with literature values. AUC0.t and AUC0–∞ „ of 5-ISMN tablet and intravenous infusion were 2694 ± 496 ng · ml−1 h vs. 2548 ± 556 ng · ml−1 · h and 3266 ± 624 ng · ml−1 · h vs. 3178 ± 769 ng · ml−1 h, respectively, and the relative bioavailability of 5-ISMN tablet was 105 ± 20 %. As compared with 5-ISMN intravenous infusion, ISDN can rapidly reach the plateau concentration and metabolize to its active metabolites 5-ISMN and 2-ISMN, which both have vasodilator effect. The results of this study suggest that as evaluated from the pharmacokinetic profiles of the three formulations, 5-ISMN tablet and ISDN intravenous infusion are ideal vasodilators and anti-angina drugs especially in acute conditions due to their rapid onset and long duration of action.
Keywords: CAS 87-33-2; CAS 16051-77-7; Isosorbide dinitrate, clinical studies, pharmacokinetics, relative bioavailability; Isosorbide 5-mononitrate, clinical studies, pharmacokinetics, relative bioavailability